Faktor-Faktor Yang Mempengaruhi Masyarakat Berhubungan Dengan Rentenir - Irma Novida; Dede Dahlan (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2020)
This research was carried out to find out more deeply, and to analyze what factors affected the village community in relation to loan sharks so that in the future there would be no more village communities to deal with rentenier. But they are more likely to choose banks that are both conventional banks and Islamic banks. The research method used is by submitting direct interviews and by distributing questionnaires to village communities where researchers conduct their research. Data analysis techniques with multiple regression with SPSS Version 2.2 program. The results showed that the need factors, religious factors, guarantee factors and the ease of factors that had a significant effect on the community were related to rententir both partially and simultaneously.